THE UTILIZING OF RECYCLED PLASTIC WASTE AS AN ALTERNATIVE FOR ZERO CEMENT PAVING BLOCKS - Mustakim, Mustakim; Asrul, Asrul; Virlayani, Asnita (Jurnal Teknik Sipil, 2023)
The problem of plastic waste that needs to be handled and managed optimally can cause environmental damage. This study aims to test the compressive strength and water absorption value of paving blocks made of plastic which are designed using a mixed variation of V50-50 (50% sand, 50% plastic), V25-75 (25% sand, 75% plastic) and V0-100 (0% sand, 100% plastic) of the total proportion of the paving blocks mix. The method is carried out by melting PP (Polypropylene) mineral glass plastic, mixing with sand based on variations, printing according to the size of the paving block, and using as a test sample in the form of a dice. The average compressive strength test results show that the model with code V25-75 has a relatively higher compressive strength value than V50-50 and V0-100. The average compressive strength value of the sample with code V25-75 is 11.53 MPa, followed by code V50-50 of 9.63 MPa, and the lowest is coded V0-100 of 3.70 MPa. The compressive strength value is influenced by the optimal percentage between sand and plastic; plastic serves as a binder for sand in a mixture of paving blocks. The rate of water absorption value will continue to decrease along with the addition of plastic waste in the paving block mixture; V50-50 is 1.44, V25-75 is 0.88, and V0-100 is 0.16. This research is expected to be applied by the community to make paving block products to reduce the amount of plastic waste globally.